1997
DOI: 10.1177/088307389701200102
|View full text |Cite
|
Sign up to set email alerts
|

Study of Nerve Conduction and Late Responses in Normal Chinese Infants, Children, and Adults

Abstract: Healthy Chinese individuals (n = 168), aged from 24 hours to 30 years, were studied to establish the following normal values: (1) motor conduction velocity, distal latency, amplitude, and F-wave velocity in the median, ulnar, tibial, and peroneal nerves; (2) H-reflex velocity and latency in the tibial nerve for all subjects as well as in the median and ulnar nerves in infants; (3) sensory conduction velocity, latency, and amplitude in the median, ulnar, and sural nerves; and (4) the difference in minimal laten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 6 publications
1
40
1
Order By: Relevance
“…Studies have proved that the motor and sensory conduction velocities in new born were 40% to 50% of adult values and at 3 years of age the normal values were in the adult range for all motor and sensory nerve conduction velocity. 2 Awang et al 3 observed that conduction velocity reduction with age was not very significant. Though it is agreed that aging alters nerve conduction studies, it does not clearly define the age group at which these changes occur.…”
Section: Introductionmentioning
confidence: 97%
“…Studies have proved that the motor and sensory conduction velocities in new born were 40% to 50% of adult values and at 3 years of age the normal values were in the adult range for all motor and sensory nerve conduction velocity. 2 Awang et al 3 observed that conduction velocity reduction with age was not very significant. Though it is agreed that aging alters nerve conduction studies, it does not clearly define the age group at which these changes occur.…”
Section: Introductionmentioning
confidence: 97%
“…[16] There are many crosssectional studies that have estimated the reduction in NCV ranging between 0.13 m/sec and 0.22 m/sec [17] these also point to the fact that aging has a definite effect on the NC parameters. Cai and Zhang [18] reported in their study that the conduction velocity in a newborn is approximately 50% of adult values and progressively increase, reaching the adult value at the age of three. There is an accelerated rate of decline in total number of muscle fibers commencing at the age of 25 years thereby affecting the conduction velocity.…”
Section: Discussionmentioning
confidence: 96%
“…There was no family history of neuromuscular disorders, including polyneuropathy. Electrophysiological examination at 11 years of age showed low amplitudes of compound muscle action potential (CMAP) and slow motor nerve conduction velocities (MCV) ( Table 1) [2]. Although mild exacerbation and remission of symptoms reoccurred, she had been followed closely without any treatment.…”
Section: Case Reportmentioning
confidence: 98%
“…to distal and CMAP < 20% below lower limit of normal values[2]; MCV < 70% below lower limit of normal values[2]. electrophysiological examinations, genetic analysis to exclude HMSN or other genetic neuropathic disorders, other autoimmune pathogenetic analysis, and responsiveness to immunotherapy, in order to define the diagnosis of CIDP.…”
mentioning
confidence: 99%